Controllability of semilinear stochastic evolution equations in Hilbert space. (2001) - Balasubramaniam, P.; Dauer, J. P.
Abstract : Controllability of semilinear stochastic evolution equations is studied by using stochastic versions of the well-known fixed point theorem and semigroup theory. An application to a stochastic partial differential equation is given.